The association between child maltreatment and emotional, cognitive, and physical health functioning in Vietnam - Nhu K. Tran; Sheila R. Van Berkel; Marinus H. van IJzendoorn; Lenneke R.A. Alink (BMC, 2017)
Abstract Background There is a paucity of research on correlates of child maltreatment in limited-resource countries with a relatively high tolerance of harsh discipline. This Vietnamese study aimed to investigate associations between different types of child maltreatment and child emotional, cognitive, and physical health functioning as well as moderation effects of gender and ethnicity. Methods This cross-sectional study was conducted with 1851 randomly selected students aged 12-17 years. Both self-report and more objective measures (weight, height, study ranking, and a memory test) were used. Results All types of child maltreatment were associated with emotional dysfunctioning. Life time and past year experiences of physical abuse and life time experiences of sexual abuse and neglect were related to poorer perceived physical health. The study did not find associations between any type of child maltreatment and overweight or underweight status. Regarding cognitive functioning, life time experience of sexual abuse and neglect were related to poorer working memory performance. Noticeably, emotional abuse was related to better academic performance, which might be an indication of "tiger parenting" practice in Vietnam, implying academic performance stimulation at the expense of emotional security. No significant moderation effects by gender and ethnicity were found. Conclusion Even in a culture in which harsh discipline is normative, child maltreatment was related to negative aspects of child wellbeing including emotional, cognitive, and physical health functioning. Efficient and low-cost interventions on child maltreatment should be developed and conducted in Vietnam as well as other countries with similar contexts.